Infill Architecture as a Solution for Livability and Historical Texture Quality Promotion - Nasrollah Beiglu, Fatemeh Bayandur; Husseini Ghafari, Seyyed Mohammad; Taheri, Aazam (Salehan Institute of Higher Education, 2019)
A brief glance at the city view of Iranian historical cities shows valuable ancient textures, all of which were enjoying appropriate liveliness, mobility and hilarity no longer ago. Today, our urban worn out textures are abandoned due to different reasons. This is while, if the textures enjoy safe, appropriate and lively spaces, organized joy and healthy recreations compatible with the society’s values will take place in them. Organizing cities and historical textures is of great importance for two reasons: one is respecting the elders’ heritages and the other one is obviating limits caused by urban texture decay. Inattention to organizing and restoring worn out historical textures plans during several years have caused them to lose their liveliness, efficiency and former activity. Livability is one of the greatest urban planning ideas in the contemporary period. Livability creation among cities of developing countries is a concerning issue and paying less attention to the issue causes liveliness and livability cadence and texture decay, consequently. Hence, paying attention to life quality, conditions, equipment and the urban residents’ needs are vital issues. Finally, infill solution is presented in the framework of renovation and improvement for promotion of quality and empowerment of historical and worn out urban textures along with influential factors of developing such textures.